Cognitive impairment in spinocerebellar ataxia type 12. (April 2021) - Agarwal, Amit; Kaur, Harsimarpreet; Agarwal, Ayush; Nehra, Ashima; Pandey, Shivam; Garg, Ajay; Faruq, Mohammed; Rajan, Roopa; Shukla, Garima; Goyal, Vinay; Srivastava, Achal Kumar
Abstract: Introduction: Cognitive impairment has now been recognised to be present in patients with several of spinocerebellar ataxias (SCAs). Cognitive impairment in patients with spinocerebellar ataxia type 12 has not been evaluated. Objective: To evaluate the cognitive impairment in patients diagnosed with spinocerebellar ataxia type 12 (SCA12). Methods: We conducted a cross sectional study and enrolled 30 (20 male and 10 female) genetically confirmed SCA12 patients and 30 healthy, age, gender and education matched individuals as controls. Cognitive domains were tested using a battery of validated neurocognitive tests. Result: Mean age of patients was 51.6 ± 8.0 years and mean disease duration was 5.3 ± 3.0 years. Mean International Cooperative Ataxia Rating Scale (ICARS) score was 29.8 ± 12.5. SCA 12 patients scored significantly lower than controls in executive function and new learning ability. Other tested cognitive domains were also affected but did not reach statistical significance. Age, age at onset, severity of ataxia, disease duration and CAG repeat length did not correlate with cognitive impairment. Conclusion: Cognitive impairment is a part of the spectrum of SCA12 and is characterized by dysfunction in executive function and new learning ability even early in the course of disease. Highlights: Very few studies have evaluated the cognitive aspect of SCAs and have reported a wide variety of cognitive impairments. We did a case control study for cognitive assessment in SCA12, which is clinico- pathologically unique amongst SCAs. A significant impairment in new learning ability and executive function was demonstrated, even early in the illness. Study hints toward need of individualized cognitive rehabilitation interventions and compensatory rehabilitation strategies.